Haematology of captive grey-brocket deer Mazama gouazoubira (Fischer, 1814) (Cervidae: Odocoileinae) - Hoppe, Estevam Guilherme Lux [UNESP] (2010)
Reference intervals for haematologic and total plasma proteins profiles were determined for 11 physically restrained adult grey-brocket deer. Erythrocytic alterations, as discrete to moderate poikilocytosis, were observed in all animals. Red and white blood cells counts were determined by manual methodology. Obtained erythron and leukon values were slightly higher than previous reports. Statistical difference was not demonstrated between stags and hinds. No previous studies reported blood values for captive grey-brocket deer obtained by manual methods. Also, the authors suggest that future studies on deer haematology should be focused on technique evaluation and improvement, considering the unusual erythrocytic morphology. © Springer-Verlag London Limited 2009.